Video Led Learning for Agri-Nutrition Education: A Participatory Assessment - Satyapriya , Premlata Singh , V.Sangeetha , V. Lenin , Sudipta Paul , and S. Barua, (Indian Journal of Extension Education, 2017)
Health is a core concept for quality life. Today's greatest challenge is to provide sufficient and healthy food to all. There islack of nutrition knowledge and practices that develop healthy habits. To attain good health, nutrition education has beenrealised as one of the essential means of helping people to improve and maintain their health. Today electronic media hasbecome an effective tool to impart knowledge. Video based material boost the knowledge and motivate people indeveloping healthy habits. Educating people with video has been proved to be very effective as it combines the senses ofseeing, hearing and text together. Studies have revealed that video extension has the advantage of credibility especiallyamong low literate people. Information has great impact when combined with educational tools. The aim of the study wasto assess the effectiveness of nutritional videos among farm women. Semi- interviews were conducted among42 respondents of Lachoda village of Baghpat district to measure the effectiveness of video presentation. The study wascarried out by using videos on semi-stiuetined to assess the effectiveness of the method in terms of video content design,logistics and learning out comes. Avideo programme was specially developed for this purpose. The data were analysed bythe specially developed effectiveness index, besides descriptive statistics including mean and standard deviation to assessthe level of effectiveness of prepared videos. It was found that the video was highly effective in its all parameters. Thecontent and design of the videos were found highly effective with the effectiveness score 86.71 and 82.90, respectively.Learning outcomes of the videos were also high. After watching the videos, the farm women were in the opinion that theycan take care of their family nutrition and they will like to explore more videos on this aspect. The results have indicatedmore positive attitude of the respondents towards the videos. Overall effectiveness score of videos was found 83.70. It wasobserved that about nutritional videos have the capacity to increase nutritional knowledge among low literate population,especially rural women.